Inverse orbital Hall effect and orbitronic terahertz emission observed in the materials with weak spin-orbit coupling - Ping Wang; Zheng Feng; Yuhe Yang; Delin Zhang; Quancheng Liu; Zedong Xu; Zhiyan Jia; Yong Wu; Guoqiang Yu; Xiaoguang Xu; Yong Jiang (npj Quantum Materials, 2023)
Abstract The Orbital Hall effect, which originates from materials with weak spin-orbit coupling, has attracted considerable interest for spin-orbitronic applications. Here, we demonstrate the inverse effect of the orbital Hall effect and observe orbitronic terahertz emission in the Ti and Mn materials. Through spin-orbit transition in the ferromagnetic layer, the generated orbital current can be converted to charge current in the Ti and Mn layers via the inverse orbital Hall effect. Furthermore, the inserted W layer provides an additional conversion of the orbital-charge current in the Ti and Mn layers, significantly enhancing the orbitronic terahertz emission. Moreover, the orbitronic terahertz emission can be manipulated by cooperating with the inverse orbital Hall effect and the inverse spin Hall effect in the different sample configurations. Our results not only discover the physical mechanism of condensed matter physics but also pave the way for designing promising spin-orbitronic devices and terahertz emitters.